2015
DOI: 10.1007/s11357-015-9774-0
|View full text |Cite
|
Sign up to set email alerts
|

Aging, glucocorticoids and developmental programming

Abstract: Glucocorticoids are pleiotropic regulators of multiple cell types with critical roles in physiological systems that change across the life-course. Although glucocorticoids have been associated with aging, available data on the aging trajectory in basal circulating glucocorticoids are conflicting. A literature search reveals sparse life-course data. We evaluated (1) the profile of basal circulating corticosterone across the life-course from weaning (postnatal day-PND 21), young adult PND 110, adult PND 450, mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
43
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 24 publications
(29 reference statements)
4
43
0
2
Order By: Relevance
“…The fall in corticosterone between 450 and 650 days confirms our finding reported previously (Zambrano et al . ). In male MOF 1 by PND 110 the DHEA:corticosterone ratio was already at its lowest level observed, so we cannot determine the timing of any life course associated fall in the ratio without data prior to 110 days.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…The fall in corticosterone between 450 and 650 days confirms our finding reported previously (Zambrano et al . ). In male MOF 1 by PND 110 the DHEA:corticosterone ratio was already at its lowest level observed, so we cannot determine the timing of any life course associated fall in the ratio without data prior to 110 days.…”
Section: Discussionmentioning
confidence: 97%
“…We have found that it is preferable to evaluate subjects at at least four ages, spread over as much of the life course as possible, that occur with normative ageing in control offspring (CF 1 ) of normally fed mothers (Zambrano et al . ). The more time points evaluated the stronger the conclusions.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…By binding to glucocorticoid receptor (GR), almost ubiquitously expressed, GCs become pleiotropic regulators of multiple cell types, with a wide range of roles in both healthy and diseased individuals [10], assuming a critical role in physiological systems [11].…”
Section: Introductionmentioning
confidence: 99%